HOUSEHOLD INWARD REMITTANCES AND PRODUCTIVE INVESTMENT IN NIGERIA: A MULTIDIMENSIONAL ANALYSIS - Ezike, John Emeka; Ogboi, C. (Advances in Social Sciences Research Journal, 2017)
There has been an unprecedented inflow of household inward remittances into the Nigerian economy over the recent years however there are concerns about the use of inward remittances for productive investment or consumption of imported goods. This study sought to empirically examine the effect of household inward remittances on productive investments in Nigeria. Generalized Method of Moment (GMM) estimator was used to analyze time series data sourced from World Development Indicators (WDI) 2015 edition. Results showed that; (i) inward remittances have negative and significant impact on productive investment in Nigeria, (ή= -0.0617; p=0.0279) (ii) inward remittances have positive and significant impact on consumption (Ώ=0.0330; p=0.0365), (iii) Consumption exert positive and significant impact on imported goods ( λ=1.018; p=0.0241). The study therefore concluded that inward remittances discourage productive investment and boost consumption of imported goods. This could be attributed to the seeming resource transfer to consumption of imports arising from price differentials between locally manufactured goods to foreign imports. To plug this leakage, it becomes imperative for Nigerian government to dismantle all bureaucratic bottlenecks that make cost of production high. It is recommended that Nigerian government should begin to build infrastructure and subsidize production as against subsidizing consumption such as proposed school feeding and fuel Subsidy